Okoljska kriza: Izzivi in priložnosti za krepitev odpornosti - Rutar, Minea; Plohl, Nejc; Horvat, Marina; Tement, Sara; Musil, Bojan; Bakračevič, Karin (Komuniciranje okoljske krize, 2025)
In present chapter, we discuss the key psychological factors that influence the likelihood of pro‑environmental behavior and the challenges that prevent it. In the first part, we introduce the theory of planned behavior, which explains how changing beliefs, environmental awareness, subjective norms, and behavioral intentions contribute to effectively confronting climate change. The second part focuses on the emergence of climate anxiety and the psychological interventions most commonly employed to address it. We outline the multiple‑needs approach and highlight the differences between various types and levels of intervention, as well as their role in fostering and strengthening resilience in both individuals and communities.